Echoes of Scripture in the letters of Paul - Hays, Richard B. (New Haven Yale UP, 1989)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Epistles of Paul -- relation to the Old Testament; Bible. O.T. -- quotations in the New Testament; Bible. N.T. Epistles of Paul -- criticism, interpretation, etc